Effect of Linear Alkylbenzene Sulfonate on Mortality, Hatching Rate of Eggs and Abnormality of Catfish (Pangasius hypophthalmus Sauvage) Larvae - E. Supriyono; L. Lisnawati; D. Djokosetiyanto (Jurnal Akuakultur Indonesia, 2007)
Linear alkylbenzene sulfonate (LAS) surfactant in the water can affecting fish in all developmental stages.  This study was aimed to observe the effect of LAS on mortality, hatching rate of eggs, and abnormality of patin catfish (Pangasius hypophthalmus Sauvage) larvae.   Fertilized eggs were incubated in water containing LAS at the dosages of 0.0, 0.5, 1.5, 3.0, 9.0, and 18.0 mg/L.  Eggs mortality was observed every 6 hours until larvae hatched (24 hours).  The results of study showed that the exposure of 18.0 mg LAS per liter water could put to death all the fertilized eggs and larvae be abnormal.  The exposure of LAS at concentration of 9.0 mg/L could kill 98% of eggs and hatching rate was only 2%.  The abnormality in larvae was bending in the body and tails.